The chosen queen : a novel of the Pendragon prophecy - Davey, Sam (Davey, Sam. The Pendragon Prophecy, 2025)
"Igraine, destined mother of King Arthur, takes center stage for a powerful, feminist retelling of Camelot.The stories of Camelot do not begin with the sword in the stone-but rather with a twisted chain of murder, magic, and deceit.A Welsh princess educated on the Lake Isle of Avalon, Igraine is now happily married to the Cornish War Duke Gorlois, a match arranged for political advantage that blossomed into love. When Gorlois begins to forsake the ancient magics, however, it creates a strain between them, as well as friction between Igraine and Vivian, the Lady of the Lake and High Priestess to the Goddess. While Igraine and Gorlois are visiting Uther Pendragon, King of Britain, at his castle, Uther makes it obvious to the entire court that he desires Igraine to be his queen. Later, he accosts her in the castle corridors, and when Igraine informs Gorlois of what happened, her husband gathers his people and abruptly leaves the festivities, declaring war. England has only recently found peace, and Merlin pleads with Gorlois to pledge allegiance to Uther. He speaks of a prophecy that reveals Igraine's son is destined to wield the mighty sword Excalibur and unite the British Isles. He will be the fabled Once and Future King. But the prophecy does nothing to dissaude Gorlois, whose pride will keep him bent toward war, no matter the cost to his people.In the bloody aftermath of civil war, Igraine bravely assumes the role of leader at Tintagel Castle, encouraging the women left behind to continue working the fields to show their devotion to the Goddess and instructing her two daughters, Morgause and Morgan, to harness their own powers. She plans a grand summer Solstice celebration, inviting their allies. On the eve of the Solstice, Gorlois unexpectedly returns to Tintagel. But it is only after she lies with who she believes is her beloved husband that Igraine learns the full extent of Merlin and Vivan's devious plot.Igraine is chosen by the Goddess, by the Lady of the Lake, by Merlin, by Uther Pendragon . . . but in the end, she will choose her own destiny, and in doing so, inadvertently set the stage for the blood-feud that will become the canker at the heart of Camelot." -Amazon.